Entrepreneurial Attitudes and Their Influences on Business Performance of Dawet Sellers in Banjarnegara, Central Java, Indonesia - Siti Jahroh; Indriyani Ida Suprapti (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
In the perspective of regional development, traditional cuisine is one of the potentials of each region in Indonesia. For example, Banjarnegara with dawet, a traditional drink that has a great potential for further development. The purpose of this study was to determine the entrepreneurial attitudes of dawet sellers and to analyze the influence of their attitudes on the success of the dawet business in this district. Partial Least Square method was used in this study, and data was collected during the period of May-August 2016 with a total of 32 respondents. The results show that honesty, discipline, commitment and creativity are all significantly and positively correlated with entrepreneurial attitudes. The indicators of the success of the dawet business that are significantly and positively correlated are the increase in sales value, income, and profits, as well as the fulfillment of household daily needs of dawet sellers. So, in overall, entrepreneurial attitudes are significantly and positively correlated with the success of the dawet business.